Hubungan Dukungan Keluarga Tentang Makanan Rendah Garam Dengan Derajat Hipertensi Pada Lansia di Desa Tunggorono Kecamatan Jombang Kabupaten Jombang - Muhammad Alif Rusdi Suryana; Prasetyo R; Heni Maryati (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
Hypertension referred to one of degenerative diseases with high morbidity and mortality especially for elderly (Samtosa, 2014). The lack of family support dealing with low-salt diet caused the blood pressure higher. This study aimed to investigate the correlation family support regarding to low-salt diet and hypertension level toward elderlies in Tunggorono, Jombang. This study applied correlational design with cross-sectional approach. The population used was 138 elderlies. Furthermore, this study used 35 elderlies through cluster random sampling technique. The data collection was obtained through questionnaire, in order to measure the family support, and observation utilizing blood pressure gauge, in order to measure their blood pressure. The data analysis was conducted through Spearman Rank statistical test. The result of this study found that almost a half of the respondents (42.9%) had mild-level family support regarding to low-salt diet, while most of the respondents (52.4%) were stage-1 hypertensive. the Spearman Rank statistical test resulted 0.000, in which less than 0.05, stating that H0 was rejected and H1 was accepted. Thus, it indicated that there was correlation between family support regarding to low-salt diet and hypertension level toward elderlies in Tunggorono, Jombang. The Spearman Rank correlational value was 0.594, in accordance to the interpretation table, it was in the range of 0.400–0.599, referring to mild interpretation. An appropriate family support in order to meet the low-salt diet could be an influential factor dealing with hypertension level. Providing education of health to the community would bring a positive impact in expanding their insight to meet their dietary needs in accordance to the principle of proper low-salt dietary habit, to lessen the high blood pressure, and to improve the health of the elderlies..Keywords : Family Support, Low-Salt Diet, Hypertension, Elderlies.